THE ROLE OF THE ENVIRONMENT IN CHILDHOODS LANGUAGE DEVELOPMENT - Sijabat, Intan Cezya; Damanik, Bernieke Anggita Ristia (Sindoro: Cendikia Pendidikan, 2025)
The environment plays a crucial role as a platform in the development of children's language and speech skills, as it is part of their interactions during the developmental process. This research aims to describe the role of the environment in children's language development. The method used in this research is qualitative, employing a literature review approach. Sources are taken from various kinds of literature, including journals, articles, previous research, and other internet sources. The results of this study show that the role of the environment is very important in language development because early childhood language skills can develop depending on the stimuli provided by the environment. The environment helps train children in communication by introducing proper greetings, familiarizing them with surrounding objects, implementing democratic parenting, and integrating language skills into daily life, thereby supporting children's ability to express themselves.